Adoption of improved dairy husbandry practices by the dairy farmers of Sundarpukhuri Milk Co-operative Society, Nazira, Sivasagar, Assam, India. - Islam, Rafiqul (Indian Journal of Dairy Science, 2015)
A study was conducted among the dairy farmers of Sundarpukhuri Milk Co-operative Society to assess the level of adoption of improved dairy husbandry practices. For the purpose a total of one hundred numbers of farmers were selected randomly from two villages under the society. The various data regarding adoption level of improved breeding, feeding, health care management and marketing practices were collected by personal interview methods in a pre-structured interview schedule. It was found that 95 per cent of the farmers adopted artificial insemination while only 6.5 per cent of the farmers adopted natural service by improved bulls. The overall adoption of improved breeding practices was 75.64 per cent with the mean score of 1.51. It was also found that 66.0 percent of the farmers adopted feeding of mineral mixture. The overall adoption of improved feeding practices was 43.57 per cent with the mean score of 0.87. The data indicated that out of seven improved practices included in health care, regular cleaning and disinfection of shed got highest adoption index (95.5) and ranked the first. The practice of selling milk to the co-operatives ranked the first with mean score of 1.94 and adoption index of 97.0 percent followed by regular selling of milk, checking quality at collection point, obtained loans from banks instead of village moneylenders and so on. The overall mean score and adoption index for improved marketing practices were 1.30 and 65.35 percent respectively. Â Â